2010
DOI: 10.1111/j.1365-2621.2009.02130.x
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of tortellini meat filling by histology and image analysis

Abstract: The aim of this study was to identify the presence of different animal tissues in tortellini meat-filling with special emphasis on the percentage of skeletal muscle. Industrially packed and refrigerated tortellini filling from four different Italian commercial brands were examined and compared. From each brand, five different batches were sampled at intervals of 1 month. From each batch, four fillings were randomly sampled and coded to allow a blind examination. Histological sections were examined to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In this study, skeletal muscle, adipose and connective tissue allowed to be present in sausage samples and animal tissues that are not legally allowed to be added to the sausage dough were detected in all of the fermented sausage samples. Although skeletal muscle and connective tissue are the main components found in sausages, the quality of sausage is closely related to the amount of these components [9]. Although a histometric measurement was not performed in this study, in the microscopic examination of the preparations, the level of the presence of connective tissue in 9 (50%) of the samples was the same or more than the muscle tissue.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, skeletal muscle, adipose and connective tissue allowed to be present in sausage samples and animal tissues that are not legally allowed to be added to the sausage dough were detected in all of the fermented sausage samples. Although skeletal muscle and connective tissue are the main components found in sausages, the quality of sausage is closely related to the amount of these components [9]. Although a histometric measurement was not performed in this study, in the microscopic examination of the preparations, the level of the presence of connective tissue in 9 (50%) of the samples was the same or more than the muscle tissue.…”
Section: Discussionmentioning
confidence: 81%
“…In studies conducted in other countries; it has been reported by Ghisleni et al [9] that nervous tissue, blood vessels, adipose tissue, upper digestive system mucosa, cartilage and glandular tissues are present besides skeletal muscle in the meat filling of tortelline, which is a popular pasta unique to Italy. Marcincak et al [29] have reported bone tissue in a traditional meat product purchased from markets in Slovakia and the Czech Republic, and Latorre et al [11] have reported presence of cartilage and lymph nodes in sausages in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histology allows the detection of specific tissue components and architectural changes promoted by distinct types of meat processing [59]. Immersion treatments change the structure of steak meat tissue, and the distance between cells increases with decreasing pH.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the contents of eight brands of hotdog [5], hamburger [6], and other meat products [4][5][6][7][8][9][10][11].…”
Section: Evaluation Of Content and Qualitymentioning
confidence: 99%